Leech Application in the Management of Chronic Wounds - DEVENDRA P. MISHRA (Dr. Chinmay Pandya, 2014)
Chronic wounds are always a major clinical challenge very frequently encountered by us in our clinical practice. These wounds are often infected with bacteria resistant to antibiotics, compounding the problem. A major problem in clinical studies of wound healing is that the factors which may affect wound healing tend to co-exist in patients, and it may be difficult or impossible to determine the significance of any one factor. So, keeping these points in mind, an elaborate review of Ayurvedic & Modern literature was done and based on the research, leech application was done on chronic wound. Results were obtained and evaluated using chi-square statistical calculations. It was observed that leech application not only improves the hypoxic condition but also provides a moist environment for wound healing.